IMPLEMENTASI E-PURCHASING DALAM PENGADAAN BARANG/JASA PEMERINTAH DI OPD KECAMATAN PRIGEN - Oktaviranti, Sabrina Amanda (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
Procurement of Government Goods/Services electronically or what is called e-purchasing in Kab. Pasuruan is regulated in SE Bupati Pasuruan No. 027/135/424.023/2023 concerning Implementation of Electronic Purchasing (E-Purchasing) in the Pasuruan Regency Government. The aim of this research is to analyze the implementation of this policy as well as the obstacles in the policy implementation process that occur in the Prigen District Regional Apparatus Organization. Using Merilee S. Grindle’s public policy implementation approach with two variables, namely Content of Policy and Context of Policy, along with derivative dimensions for each variable. This type of qualitative research and descriptive approach found data sources through primary and secondary data. This research also used purposive sampling techniques, as well as dara collection through interviews, observation and documentation. Through this research, it was found that the implementation of e-purchasing in the procurement of government goods/services in the Prigen District Regional Apparatus Organization, which refers to Merilee S. Grindle’s theory, was good and in accordance with what was desired or expectd. Obstacles in the process of implementing the e-purchasing policy were encountered during the research process as it was.